2017
DOI: 10.3758/s13420-017-0270-5
|View full text |Cite
|
Sign up to set email alerts
|

Gambling in rhesus macaques (Macaca mulatta): The effect of cues signaling risky choice outcomes

Abstract: Preference for a larger-variable “risky” option over a smaller-reliable “safe” option often depends upon the likelihood that the risky option will deliver a sufficiently sized reward to have an equivalent or superior expected value. However, preference for the risky option has been shown to increase under conditions where informative stimuli signaling the outcome of a risky choice is included between the choice and the outcome (e.g., Zentall & Stagner, 2011) and this risk-prone preference persists even when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 58 publications
5
27
0
Order By: Relevance
“…Since Kendall's (1974) initial demonstration, suboptimal choice has been extensively studied in pigeons (see McDevitt et al, 2016 andZentall, 2016b), and has been observed in monkeys (e.g., Blanchard, Hayden, & Bromberg-Martin, 2015;Bromberg-Martin & Hikosaka, 2009;Smith, Beran, & Young, 2017) and starlings (e.g., Vasconcelos, Monteiro, & Kacelnik, 2015). The procedure has also been used with rats, but the results have been less consistent (e.g., Mazur, 2007;Trujano & Orduna, 2015; but see Cunningham & Shahan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since Kendall's (1974) initial demonstration, suboptimal choice has been extensively studied in pigeons (see McDevitt et al, 2016 andZentall, 2016b), and has been observed in monkeys (e.g., Blanchard, Hayden, & Bromberg-Martin, 2015;Bromberg-Martin & Hikosaka, 2009;Smith, Beran, & Young, 2017) and starlings (e.g., Vasconcelos, Monteiro, & Kacelnik, 2015). The procedure has also been used with rats, but the results have been less consistent (e.g., Mazur, 2007;Trujano & Orduna, 2015; but see Cunningham & Shahan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, rhesus macaques exhibit robust risk-seeking behaviour in the gain domain [81][82][83][84][85][86][87][88][89][90]. Risk-seeking attitudes have also been reported in the loss domain [91]. Risk-seeking behaviour in experience-based studies can be computationally explained by an increased sensitivity to positive (compared to negative) prediction errors ('positivity' bias) as the one generally documented in humans (Box 1) [67,92,93].…”
Section: Decision Under Risk In Monkeysmentioning
confidence: 99%
“…Past research has demonstrated preference for an alternative which produces stimuli that signal the future presence or absence of reinforcement over an alternative which does not produce reinforcement-predictive stimuli. This preference has been found in multiple species, including capuchins, rhesus macaques, pigeons, and rats ( Roper and Zentall, 1999 ; Smith et al, 2017 ; Cunningham and Shahan, 2019 ; Smith and Beran, 2020 ). For example, when Roper and Zentall (1999) presented a choice between two alternatives which produced reinforcement equally 50% of the time, pigeons’ choices were more frequently allocated to the alternative which provided reinforcement-predictive stimuli (see Figure 1A ).…”
Section: Introductionmentioning
confidence: 95%
“…When a similar study was conducted with rhesus macaques, subjects were more likely to choose a risky option which gave reinforcement less often if the outcomes were signaled ( Smith et al, 2017 ). That is, with experience, macaques chose suboptimally more often if stimuli predictive of reinforcement outcomes followed those choices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation